Possible Solutions to the World Crisis. An Accounting Perspective - Daniela Ciotina; Cristina-Ionela Fadur (CES Working Papers, 2010)
Purpose – Our aim is to seize the essential aspects of the economical-financial environment and the alternatives that the companies have in their confrontation with the current challenges, the reorganization of the company being regarded as an option for ensuring the continuity of their activity. We have also been interested in the issue of intangible assets, which lie at the basis of the process of value creation by the company. Methodology – The article is a critical review of the process of reorganization and of the importance of the intangible asset, providing a personal perspective. Conclusions – The process of reorganization is no longer an option, but an essential condition for avoiding the disappearance of the companies from the market.
Keywords: 330; reorganization; reengineering; mergers; intangible assets; economic crisis